2007
DOI: 10.2164/jandrol.106.001701
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Semen Quality Associated With Environmental DDT Exposure in Young Men Living in a Malaria Area in the Limpopo Province, South Africa

Abstract: The pesticide DDT [1,1,1-trichloro-2,2-bis(chlorodiphenyl)ethane] is 1 of the 12 persistent organic pollutants (POPs) under negotiation at the Stockholm Convention to restrict or ban their production and use because of their toxicity, resistance to breakdown, bioaccumulation, and potential for being transported over long distances. DDT has estrogenic potential, and the main metabolite, p,p9-dichlorodiphenyl-dichloroethylene (p,p9-DDE), is a potent antiandrogen. In response to mounting evidence on the endocrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
152
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(160 citation statements)
references
References 71 publications
6
152
0
2
Order By: Relevance
“…p,p′-DDT, an estrogenic endocrine disrupting chemical, and its anti-androgenic metabolite, p,p′-DDE, have been linked to male reproductive health effects Aneck-Hahn et al, 2006). DDT and/or DDE have also been linked with post generational female reproductive ability (Cohn et al, 2003), urogenital birth defects in neonates (Bornman et al, 2005) and pre-term births (Longnecker et al, 2001).…”
Section: Human Serummentioning
confidence: 99%
See 1 more Smart Citation
“…p,p′-DDT, an estrogenic endocrine disrupting chemical, and its anti-androgenic metabolite, p,p′-DDE, have been linked to male reproductive health effects Aneck-Hahn et al, 2006). DDT and/or DDE have also been linked with post generational female reproductive ability (Cohn et al, 2003), urogenital birth defects in neonates (Bornman et al, 2005) and pre-term births (Longnecker et al, 2001).…”
Section: Human Serummentioning
confidence: 99%
“…Although some studies have found little evidence for a link between DDT exposure and health effects, (Cocco et al, 2005(Cocco et al, , 2006, other studies have shown that DDT and its metabolites may have adverse health effects in humans (e.g. Beard, 2006;IPEP, 2006;Aneck-Hahn et al, 2006;Eskenazi et al, 2009). However, limited data is available on the levels of DDT exposure experienced by those living in sprayed homes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from South Africa found reduced retinol-binding protein and thyroid hormone concentration, urogenital malformations in newborn boys, and impaired semen quality, associated with non-occupational exposure to DDT (Aneck-Hahn et al, 2007;Bornman et al, 2010;Delport et al, 2011).…”
mentioning
confidence: 99%
“…[17][18][19] Therefore, one should be aware of the possibility that the lack of community involvement in an existing community-passive malaria control system may also become a problem when promoting measures to reduce exposure to IRS chemicals 27 , as some of these are likely to involve behavioural changes.…”
Section: Discussionmentioning
confidence: 99%
“…Formal employment opportunities are few, and many are subsistence farmers. [16][17][18] Based on aerial photographs, random starting points for systematic homestead sampling were identified. Because the villages are informally planned and homesteads are often without clear site boundaries, it was impossible to derive a precise number of homesteads for each village.…”
Section: Study Area Description and Populationmentioning
confidence: 99%